(untitled) (CONOCIMIENTO, INVESTIGACIÓN Y EDUCACIÓN CIE, 2024)
Educational inclusion is a model that has been developed in different countries and that Colombia has sought to incorporate into the country’s educational policies with different strategies. And since 2009, different strategies have been presented that seek not only coverage, but educational quality for all students. In this way, for the educational inclusion of the migrant Yukpa indigenous population from the Nuevo Escobal settlement in the city of Cúcuta, the Municipal Education Secretariat has been based on the legal framework to operate with different strategies for the aforementioned indigenous student population.